Seasonal and nutritional changes in the short form of the leptin receptor expression and VEGF system in the choroid plexus, arcuate nucleus, and anterior pituitary in MTS-leptin and resistin-treated sheep - Dorota Anna Zieba; Weronika Biernat; Malgorzata Szczesna; Katarzyna Kirsz; Tomasz Misztal (Frontiers in Neuroscience, 2023)
The short form of the leptin receptor (LeptRa) plays a key role in the transport of leptin to the central nervous system (CNS). Here, MTS-leptin and recombinant ovine (ro) leptin-mediated expression of LeptRa and VEGFA and VEGFR2 concentration in selected hypothalamic nuclei, choroid plexus (ChP), and anterior pituitary (AP) were analyzed considering the photoperiod and acute-fasting (experiment 1), and nutritional status (experiment 2) of ewes. In experiment 1, 60 sheep were fed normally or fasted for 72 h and received one injection of saline, MTS-leptin, or roleptin 1 h prior to euthanasia. LeptRa mRNA transcript levels and VEGF system protein concentrations were detected in the ARC, ChP predominantly in the SD, and AP for the LD without detection of LeptRa in the POA and VMH/DMH. In experiment 2, an altered diet for 5 months created lean or fat sheep. Twenty sheep were divided into four groups: the lean and fat groups were given saline, while the lean-R and fat-R groups received resistin 1 h prior to euthanasia. Changes in adiposity influenced the lowering effect of resistin on the expression of LeptRa and VEGF system protein concentrations. Overall, both photoperiodic and nutritional signals influence the effects of MTS-leptin/roleptin and resistin-mediated leptin transport to the CNS via LeptRa. Resistin seems to be another adipokine involved in the adaptive/pathological phenomenon of leptin resistance in sheep.